A comparative study on thermomechanical and rheological characteristics of graphite/polypropylene nanocomposites: Highlighting the role of mixing. Issue 1 (10th June 2014) - Fasihi, Mohammad; Garmabi, Hamid; Reza Ghaffarian, Seyed; Ohshima, Masahiro
Abstract : The thermomechanical and rheological properties of various graphite/long‐chain branched polypropylene (PP) nanocomposites prepared by different mixing methods have been addressed in the current work. To improve the degree of dispersion of graphite throughout the PP domains, solid‐state milling was carried out and followed by low‐temperature melt processing in the range of melting point and the crystallization temperature of PP. As a result, the well‐dispersed graphite/PP nanocomposites revealed a higher degree of plastic deformation and energy to break in the tensile test; moreover, interestingly, nanocomposites based on branched PP showed a lower zero shear viscosity and lower isothermal crystallization rate. It was speculated that the unexpected decrease in zero shear viscosity arose from the disentanglement of the long‐chain branches in particular, when an exfoliated morphology existed within the PP matrix. J. VINYL ADDIT. TECHNOL., 21:12–17, 2015. © 2014 Society of Plastics Engineers